Flow diverters for the posterior inferior cerebellar artery aneurysms: A systematic review and a single-arm meta-analysis. Issue 4 (August 2022) - Liu, Xiang; Bao, Kunyang; Luo, Wenzhang; Wan, Weifeng; Peng, Tangming; Huang, Changren
Background: The treatment of posterior inferior cerebellar artery aneurysms is controversial. Recently, flow diverters have emerged as an attractive treatment option. Here, we performed a systematic review and meta-analysis of the angiographic and clinical outcomes of flow diverter-treated posterior inferior cerebellar artery aneurysms. Methods: We searched the PubMed, EMBASE and Web of Science databases for studies published from inception to January 2021. We included studies that described flow diverters procedures for posterior inferior cerebellar artery aneurysms with ≥2 patients. The outcomes were the complete occlusion rate and flow diverter-related complication rate. Meta-analysis was performed using a random or fixed effects model based on heterogeneity. Results: We included six studies involving 46 posterior inferior cerebellar artery aneurysms. There were 14 ruptured aneurysms. All flow diverters were successfully released and the technical success rate was 100%. The complete occlusion rate was 81% (95% confidence interval = 65–93%; I 2  = 0.00%; P  < 0.01). The flow diverter-related complication rate was 18% (95% confidence interval = 5–36%; I 2  = 0.00%; P  < 0.01). One patient died of rebleeding. The mortality rate was <1% (95% confidence interval = -1–1%; I 2  = 0.00%; P  = 0.951). Conclusions: Treatment of posterior inferior cerebellar artery aneurysms with flow diverters is feasible and carries a high degree of technical success. However, this treatment is underutilized in patients with posterior inferior cerebellar artery aneurysms due to a higher complication rate and lower occlusion rate compared with clipping and traditional endovascular treatment. Further well-designed prospective and randomized studies are required to fully understand the effects of flow diverters especially in posterior inferior cerebellar artery aneurysms patients requiring endovascular treatment.